PENGARUH KONDISI POLIMERISASI TERHADAP SIFAT-SIFAT OPTIS FILM POLI o-TOLUIDIN SEBAGAI SENSOR pH - W., Endang Asijati; Susanto, Dieky; Tockary, Theofilus A; Sabarinah, Yanti (UI Scholars Hub, 2006)
The Influence of Polymerization Condition to Optical Properties of Poly-o-toludine Films for PH Sensor Application. Properties of poly-o-toludine film strongly bonded to non polar substrate was studied for application as optical pH sensor. Characterization of film in various pH value is carried out by recording absorbance curve using uv-visible spectrophotometer. All poly-o-toluidine film was then found to be applicable as optical pH sensor in the pH range of 2.0- 6.0. Further computational processing by means of curve fitting into logaritmic trend will allow expansion of measurement to the pH range of 2.0-8.0. Sensitivity of pH response was highest in poly-o-toluidine film fabricate at HCl 1.0 M and at 12 hours of dipping time. This paper also studied hysteresis effect in pH response. It was concluded that poly-o-toluidine salt exposed to basic pH will not be easily regenerated. For this reason, poly-o-toluidine film will only be suitable for single usage of pH measurement.